2023
DOI: 10.1038/s43587-023-00441-x
|View full text |Cite
|
Sign up to set email alerts
|

Longevity factor klotho enhances cognition in aged nonhuman primates

Abstract: Cognitive dysfunction in aging is a major biomedical challenge. Whether treatment with klotho, a longevity factor, could enhance cognition in human-relevant models such as in nonhuman primates is unknown and represents a major knowledge gap in the path to therapeutics. We validated the rhesus form of the klotho protein in mice showing it increased synaptic plasticity and cognition. We then found that a single administration of low-dose, but not high-dose, klotho enhanced memory in aged nonhuman primates. Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 45 publications
2
11
1
Order By: Relevance
“…α-Klotho (hereinafter abbreviated as Klotho) is a transmembrane protein related to aging. , Klotho acts as a coreceptor for fibroblast growth factor 23 (FGF23) by binding to fibroblast growth factor receptors (FGFR) 1c, 2c, and 4, to primarily regulate phosphate homeostasis in the kidney. When the extracellular domain of Klotho is cleaved by the ADAM family proteases, it is secreted into circulation as soluble Klotho . Klotho levels significantly decrease in various age-related dysfunctions, including diabetes, cancers, Alzheimer’s disease, and chronic kidney disease (CKD). In support of potential clinical relevance, it was shown that a single administration of low-dose secreted Klotho (10 μg/kg) was able to enhance memory in aging rhesus macaques . In addition, Klotho is thought to have an antifibrotic effect in CKD. , Given its role as a biomarker and a potential hormone, it is crucial to develop reagents capable of accurately detecting Klotho with high affinity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…α-Klotho (hereinafter abbreviated as Klotho) is a transmembrane protein related to aging. , Klotho acts as a coreceptor for fibroblast growth factor 23 (FGF23) by binding to fibroblast growth factor receptors (FGFR) 1c, 2c, and 4, to primarily regulate phosphate homeostasis in the kidney. When the extracellular domain of Klotho is cleaved by the ADAM family proteases, it is secreted into circulation as soluble Klotho . Klotho levels significantly decrease in various age-related dysfunctions, including diabetes, cancers, Alzheimer’s disease, and chronic kidney disease (CKD). In support of potential clinical relevance, it was shown that a single administration of low-dose secreted Klotho (10 μg/kg) was able to enhance memory in aging rhesus macaques . In addition, Klotho is thought to have an antifibrotic effect in CKD. , Given its role as a biomarker and a potential hormone, it is crucial to develop reagents capable of accurately detecting Klotho with high affinity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“… 6 9 In support of potential clinical relevance, it was shown that a single administration of low-dose secreted Klotho (10 μg/kg) was able to enhance memory in aging rhesus macaques. 10 In addition, Klotho is thought to have an antifibrotic effect in CKD. 8 , 11 Given its role as a biomarker and a potential hormone, it is crucial to develop reagents capable of accurately detecting Klotho with high affinity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Klotho-deficient mice show premature aging symptoms, including cognitive decline 3 , whereas Klotho excess extends lifespan and improves cognitive functions 4,5 . Injected Klotho enhances cognition in aged rhesus macaques 6 , while Klotho overexpression improves amyloid-β clearance and cognition in one AD mouse model 7 , and LTP and behavior in another AD model 5 . Moreover, human AD patients show lower Klotho levels in the cerebrospinal fluid (CSF) than age-matched controls 8 , contrasting a human variant that elevates the levels of the functional Klotho protein and which associates with both longevity 9 and lower AD risk 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[2] Beyond its transmembrane domain, the fibronectin type III-like extracellular domain of KL contains two tandem repeats; α-Klotho and β-Klotho, responsible for binding to fibroblast growth factor receptors (FGPRs). Secreted α-KL (sKL) circulates as a hormone after being liberated from cellular transmembrane domain and regulates various physiological processes such as wingless-related integration site (Wnt), insulin, [3] and fibroblastic growth factor (FGF) signaling, [4] mineral and cognitive homeostasis, [5] and N-methyl-D-aspartate receptor (NMDAR) function, [6] and the aging process. [7,8] α-KL is the most extensively studied isoform and is primarily expressed in brain and kidney distal tubule cells, where it controls phosphate (Pi) absorption and 1,25-dihydroxyvitamin D3 activity.…”
Section: Introductionmentioning
confidence: 99%